Improving Behavioral Health Equity through Cultural Competence Training of Health Care Providers - McGregor, Brian (Ethn Dis, 2019)
Racial/ethnic disparities have long persisted in the United States despite concerted health system efforts to improve access and quality of care among African Americans and Latinos. Cultural competence in the health care setting has been recognized as an important feature of high-quality health care delivery for decades and will continue to be paramount as the society in which we live becomes increasingly culturally diverse. Unfortunately, there is limited empirical evidence of patient health benefits of a culturally competent health care workforce in integrated care, its feasibility of implementation, and sustainability strategies. This article reviews the status of cultural competence education in health care, the merits of continued commitment to training health care providers in integrated care settings, and policy and practice strategies to ensure emerging health care professionals and those already in the field are prepared to meet the health care needs of racially and ethnically diverse populations.